2001
DOI: 10.1016/s0378-1097(01)00381-0
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of DsbA alters the behaviour of Shigella flexneri towards murine and human-derived macrophage-like cells

Abstract: The mutants of Shigella flexneri, Sh4 (dsbA: :kan) and Sh42 (dsbA33G), behave differently towards murine and human-derived macrophage-like cells in vitro. Sh4 was trapped in the phagocytic vacuoles of the murine J774 cells as evidenced by its colony forming units plus and minus chloroquine exposure in a gentamicin protection assay, and by light and transmission electron microscopy (TEM). Sh42, similar to the wild-type M90TS, was able to escape from the vacuoles and kill host cells presumably by inducing apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In contrast, the development of apoptosis or oncosis following Shigella infection of U937 cells depends on the differentiation conditions (54). When treated with phorbol myristate acetate to induce differentiation, U937 cells become tolerant to Shigella infection; the onset of oncosis is delayed until many hours after infection, allowing the recovery of large numbers of intracellular bacteria (87). To obtain intracellular bacteria, HeLa and U937 cells were infected with S. flexneri strain Sf301 under the conditions described in Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the development of apoptosis or oncosis following Shigella infection of U937 cells depends on the differentiation conditions (54). When treated with phorbol myristate acetate to induce differentiation, U937 cells become tolerant to Shigella infection; the onset of oncosis is delayed until many hours after infection, allowing the recovery of large numbers of intracellular bacteria (87). To obtain intracellular bacteria, HeLa and U937 cells were infected with S. flexneri strain Sf301 under the conditions described in Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%
“…Both media contain 10% fetal bovine serum, 2 mM L-glutamine, and penicillin-streptomycin (Invitrogen). Cells were incubated at 37°C in a humidified 5% CO 2 atmosphere as described previously (87). For bacterial infection, both cell lines were grown to 90% confluence on 120-mm-diameter plates.…”
Section: Methodsmentioning
confidence: 99%
“…Screening of the Tn5phoA mutant library of the CD-associated AIEC reference strain LF82 indicated that three mutants having an insertion of the transposon into the dsbA gene were significantly attenuated in the ability to resist macrophage killing (9). The activity of DsbA has already been reported to be necessary for many virulence phenotypes, including colonization, adhesion, invasion, and/or intracellular survival of various pathogens, such as Salmonella enterica (44), E. coli K1 (29), enteropathogenic E. coli (73), Proteus mirabilis (12), and Shigella flexneri (67,69,71). To confirm the role of DsbA in the virulence of AIEC strain LF82, a mutant with the dsbA gene deleted was constructed.…”
Section: Discussionmentioning
confidence: 99%
“…The Dsb proteins have been shown to be important in bacterial lifestyles and to play a major role in virulence in several bacterial species. The deletion variants of thiol/ disulphide oxidoreductase family members affect multiple virulence factors in several Gram-negative pathogens such as Pseudomonas aeruginosa (Ha et al, 2003), Bordetella pertussis (Stenson & Weiss, 2002), Shigella flexneri (Yu et al, 2001), Proteus mirabilis (Burall et al, 2004) and Salmonella enterica serovar Typhimurium (Miki et al, 2004).…”
Section: Introductionmentioning
confidence: 99%